Surface Current Patterns in the Northeastern Chukchi Sea and Their Response to Wind Forcing. Issue 12 (8th December 2017) - Fang, Ying‐Chih; Potter, Rachel A.; Statscewich, Hank; Weingartner, Thomas J.; Winsor, Peter; Irving, Brita K.
Abstract: We measured northeastern Chukchi Sea surface currents using high‐frequency radar systems (HFR) during the ice‐free periods of August to October from 2010–2014. We analyzed these data, along with regional winds, using Self‐Organizing Maps (SOM) to develop a set of surface current‐wind patterns. Temporal changes in the SOM patterns consist predominantly of two patterns comprising northeastward and southwestward surface currents. A third pattern represents a transitional stage established during the onset of strong northeasterly winds. These patterns are analogous to the first two eigenmodes of an empirical orthogonal function analysis of the HFR data. The first principal component (PC1) is significantly correlated (∼0.8) to that of the winds and is directly related to the time series of SOM‐derived patterns. The sign of PC1 changes when the speed of local northeasterly winds exceeds ∼6 m s −1, at which point the northeastward surface currents reverse to the southwest. This finding agrees with previous models and observations that suggest this wind threshold is needed to overcome the pressure gradient between the Pacific and Arctic Oceans. The transitional stage is characterized by alongshore currents bifurcating in the vicinity of Icy Cape and wind‐driven Ekman currents north of 71.5°N. Its development is a manifestation of interactions among the poleward pressure gradient, wind stress, and geostrophic flow due to the coastal setdown. Key Points: Surface circulation patterns under varying wind conditions during open water seasons in the northeastern Chukchi Sea are defined Northeasterly winds with magnitudes greater than 6 m s −1 reverse the northeastward‐flowing coastal current to the southwest A transitional current pattern during the onset of high magnitude northeasterly winds is described